Unlocking Agriculture Finance and Insurance in Uganda : The Financial Sector's Role in Agricultural Transformation - World Bank (World Bank, Washington, DC, 2019)
As a key pillar of the Ugandan economy, the agriculture sector is a critical driver of economic growth and poverty alleviation. Uganda's agricultural sector is dominated by smallholders with low levels of productivity. The agriculture sector is highly exposed to co-variant risks, which include weather, biological, infrastructure (post-harvest loss), price, and market risks. This plethora of risks suppresses appetite for investment in the sector. Despite the sector's contribution to the economy, farmers' access to finance remains a major constraint. Recognizing agriculture finance's critical role in the agricultural transformation agenda, the government of Uganda (GoU) is supporting several initiatives to unlock agricultural finance. To manage the financial impacts of production shocks, the GoU seeks to use agricultural insurance to derisk rural lending and expand access to rural credit for smallholders. In partnership with private insurance companies, the GoU launched the Uganda Agriculture Insurance Scheme (UAIS) as a five-year pilot in July 2016. The objectives of the scheme are to ensure that Ugandan farmers are protected against the effects of agriculture risks, especially production risks; to increase farmers' access to credit; and to make crops, livestock, and aquaculture insurance affordable to smallholder producers. The UAIS offers a range of crop, livestock, poultry, and aquaculture insurance coverage to Ugandan farmers, and is promoted by the GoU through the provision of premium subsidies. The objective of the review is to provide recommendations for enhancing the scalability and sustainability of the GoU's approach to promoting agriculture insurance in Uganda.